2022
DOI: 10.1111/apt.17226
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant‐free survival according to alkaline phosphatase and GLOBE score in patients with primary biliary cholangitis treated with ursodeoxycholic acid

Abstract: Background: After 1 year of ursodeoxycholic acid (UDCA), patients with primary biliary cholangitis (PBC) may have a normal GLOBE score despite high alkaline phosphatase (ALP) levels. Aim:To assess the association between ALP and liver transplantation (LT)-free survival according to the GLOBE score Methods: Among patients with a normal or elevated GLOBE score in the Global PBC cohort, the association between ALP after 1 year of UDCA and the risk of LT/death was assessed. The LT-free survival was compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Indeed, whereas normal ALP values in this population were consistently associated with a significant decrease in HR in the different subgroups studied, a concrete clinical benefit (ie, a significant increase in life expectancy without complications) was mainly found in the youngest patients, that is, before the age of 62 years, or those with high LSM, that is, ≥10 kPa, who together account for 60% of the study population. This inverse relationship between age and prognostic value of ALP under UDCA has been recently suggested 16 . The added value of a second-line therapy in PBC is likely to decrease with age, particularly beyond 70, especially if any ALP elevation is considered as a potential indication regardless of disease stage.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Indeed, whereas normal ALP values in this population were consistently associated with a significant decrease in HR in the different subgroups studied, a concrete clinical benefit (ie, a significant increase in life expectancy without complications) was mainly found in the youngest patients, that is, before the age of 62 years, or those with high LSM, that is, ≥10 kPa, who together account for 60% of the study population. This inverse relationship between age and prognostic value of ALP under UDCA has been recently suggested 16 . The added value of a second-line therapy in PBC is likely to decrease with age, particularly beyond 70, especially if any ALP elevation is considered as a potential indication regardless of disease stage.…”
Section: Discussionmentioning
confidence: 89%
“…Very recently, it has been shown that, even in patients with an adequate response to UDCA, normal ALP levels or total bilirubin ≤0.6 ×ULN could be associated with a further reduction in the risk of death or LT 15,16 . However, the significance of this deep biochemical response in terms of absolute clinical benefit, that is, real gains in complication-free life expectancy, and not just risk reduction, needs to be further assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBC and PSC are treated with ursodeoxycholic acid, the drug of choice for cholestatic liver disease ( 199 , 200 ). However, based on the response criteria, this treatment fails in approximately 25% to 50% of patients ( 201 ). Therefore, a large proportion of patients still do not have adequate treatment, and understanding the mechanisms of the proinflammatory pathway in AILDs and potential new therapeutic approaches is critical.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Levels of ALP and TB, alone or together, can predict liver transplantation or death in patients with PBC, with lower levels of these markers being associated with better transplant-free survival. 25,27,29 Additional treatment options for PBC are needed due to many patients lacking a complete response with or intolerance to current treatments and/ or persistent clinical symptoms that impact quality of life. 3,4,9,18,30,31 Seladelpar is a first-in-class, potent and selective peroxisome proliferator-activated receptor (PPAR)δ agonist with many effects that impact PBC, including cholestasis, hepatocellular injury,…”
mentioning
confidence: 99%